PELATIHAN DAN PENDAMPINGAN PENYUSUNAN PERANGKAT PEMBELAJARAN BERORIENTASI HOTS DENGAN PENDEKATAN TPACK BAGI GURU DI SMAN 6 PALANGKA RAYA TAHUN PEMBELAJARAN 2021/2022 - Joni Bungai; Indra Perdana; Glory Kriswantara; Riko Oktaviandra (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The activity of learning instruments development is oriented to High Order Thinking Skill (HOTS) approach based on Technological Pedagogical Content Knowledge (TPACK) was carried out at SMAN 6 Palangka Raya. This study aims to improve the technology-based learning system and to have a Learning Management System (LMS) through the implementation of community service that the researcher and team did through training and mentoring for the teachers at the school. The method used in this study is the Critical Events Model (CEM) research which was carried out for 44 educators at SMA Negeri 6 Palangka Raya. The results of the implementation of this community service research are: (1) teachers have sufficient knowledge and insight about the nature of preparing lesson plans in high school; (2) teachers have knowledge and skills in developing teaching materials; (3) teachers have knowledge and skills in developing student worksheets (LKPD); (4) teachers have knowledge and skills in making learning media; and (5) teachers have knowledge and skills in preparing learning assessment instruments